Epidermal self-powered sweat sensors for glucose and lactate monitoring - Huang, Xingcan; Li, Jiyu; Liu, Yiming; Wong, Tszhung; Su, Jingyou; Yao, Kuanming; Zhou, Jingkun; Huang, Ya; Li, Hu; Li, Dengfeng; Wu, Mengge; Song, Enming; et al. (Bio-design and manufacturing, 2022)
Sweat could be a carrier of informative biomarkers for health status identification; therefore, wearable sweat sensors have attracted significant attention for research. An external power source is an important component of wearable sensors, however, the current power supplies, i.e., batteries, limit further shrinking down the size of these devices and thus limit their application areas and scenarios. Herein, we report a stretchable self-powered biosensor with epidermal electronic format that enables the in situ detection of lactate and glucose concentration in sweat. Enzymatic biofuel cells serve as self-powered sensing modules allowing the sweat sensor to exhibit a determination coefficient ( R 2 ) of 0.98 with a sensitivity of 2.48 mV/mM for lactate detection, and R 2 of 0.96 with a sensitivity of 0.11 mV/μM for glucose detection. The microfluidic channels developed in an ultra-thin soft flexible polydimethylsiloxane layer not only enable the effective collection of sweat, but also provide excellent mechanical properties with stable performance output even under 30% stretching. The presented soft sweat sensors can be integrated at nearly any location of the body for the continuous monitoring of lactate and glucose changes during normal daily activities such as exercise. Our results provide a promising approach to develop next-generation sweat sensors for real-time and in situ sweat analysis. Graphic abstract